The Relationship Between the Severity of Head Injury and Acute Non-Epileptic Seizures in Head Injury Patients at Umar Wirahadikusumah Regional General Hospital - Pasha Aprillya Andriansyah; Hikmat Pramajati; Heri Ridwan (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2026)
Background & Objective: Head injury is a serious health problem that can cause neurological complications, including acute non-epileptic seizures. This study aimed to determine the relationship between the severity of head injury and the occurrence of acute non-epileptic seizures in patients with head injury at Umar Wirahadikusumah Regional General Hospital. Method: This study applied a quantitative cross-sectional retrospective design. The population included all head injury patients recorded in medical records from 2024 to 2025. A total 159 samples were selected using purposive sampling techniques from patients with mild, moderate, or severe head injury without a previous history of epilepsy. The research instrument was a medical record review sheet. Head injury severity assessed using the Glasgow coma scale score served as the independent variable, while acute non-epileptic seizures were the dependent variable. Data were presented descriptively and analyzed using the Spearman’s correlation test. Result: The results showed a statistically significant relationship between the severity of head injury and the occurrence of acute non-epileptic seizures, with a probability value less than 0.001 and a correlation coefficient of 0.477, indicating a positive relationship with moderate strength. Conclusion: The severity of head injury is significantly associated with the occurrence of acute non-epileptic seizures, highlighting the importance of early neurological assessment and increased clinical vigilance in patients with head injury, particularly in emergency care settings.